Експериментальне дослідження раціонального діапазону вологості сировини для брикетування - Кувачов, Володимир Петрович; Червоткіна, Олександра Олександрівна; Kuvachov, Volodymyr; Chervotkina, Oleksandra (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У статті досліджено вплив вологості сировини на фізичну щільність паливних брикетів, отриманих методом високотемпературного пресування з різних видів біомаси: деревної тирси, соломи та лушпиння соняшнику. Метою роботи було експериментальне встановлення критичного раціонального діапазону вологи для максимізації ступеня ущільнення. Експерименти проводили з п’ятьма рівнями вологості – від 4 % до 12 % – при сталих параметрах пресування. Аналіз результатів підтвердив нелінійний характер залежності з вираженим екстремумом. Найвища щільність була зафіксована при вологості 8 % для всіх зразків, досяга¬ючи ρ = 1,25т/м3 для тирси. Оптимум пояснюється ідеальною дією вологи як гідротермального пластифікатора для активації лігніну. Установлено, що відхилення від цього діапазону призводить до значного зниження щільності. /// EN: The article investigates the influence of raw material moisture content on the physical density of fuel briquettes obtained by high-temperature pressing from various types of biomass: wood sawdust, straw, and sunflower husks. The main objective of the study was to experimentally establish the critical optimal moisture range required to maximize the degree of material compaction under constant technological conditions. The experimental part included testing five clearly defined moisture levels, ranging from 4 % to 12 %, with strictly fixed pressing parameters. Analysis of the results confirmed a pronounced nonlinear dependence of density on moisture content, characterized by a clear extreme. The highest density was consistently recorded at 8 % moisture content for all samples, reaching a peak value of ρ = 1.25 t/m3 for wood sawdust. The determined optimum is theoretically explained by the ideal function of water as a hydrothermal plasticizer. At 8 % moisture content, water effectively lowers the glass transition temperature of lignin, promoting its transition to a viscous-plastic state. This ensures optimal particle deformation and the formation of strong cohesive and adhesive bonds, which guarantees the monolithic nature of the product. The study found that deviations from this critical range significantly impair the compaction process. At low levels, insufficient plasticization is observed, leading to high internal stiffness and incomplete filling of microvoids under pressure. Conversely, at high moisture levels, excess water generates high internal vapor pressure during pressing. After the external load is removed, this pressure causes elastic aftereffect and structural destruction, leading to a sharp decrease in final density and mechanical stability. The quantitative data obtained allow us to formulate practical, scientifically based recommendations aimed at standardizing and unifying the processes of raw material preparation in biofuel production, ensuring maximum product quality and energy efficiency regardless of the initial type of biomass.
Experimental study of the rational moisture range of raw materials for bricking
Keywords: брикети; сировина; брикетування; лігнін; вологість; щільність; пароутворення; температура; briquettes; raw materials; briquetting; lignin; moisture content; density; steam generation; temperature